2012
DOI: 10.4081/hr.2012.e16
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Negative Aggressive Natural Killer-Cell Leukaemia with High P-Glycoprotein Activity and Phosphorylated Extracellular Signal-Regulated Protein Kinases 1 and 2

Abstract: Aggressive natural killer-cell leukaemia (ANKL) is a rare type of disease with fulminant course and poor outcome. The disease is more prevalent among Asians than in other ethnic groups and shows strong association with Epstein-Barr virus (EBV) and P-glycoprotein (P-gp) expression associated with multidrug resistance. Here we present a case of a 47 year old Caucasian female with a prior medical history of azathioprine treated ulcerative colitis who developed EBV-negative form of ANKL. The patient presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…There are anecdotal case reports in the literature describing neoplastic proliferation of NK cells with aggressive clinical course but no EBV association. [2][3][4][5]19 Two small series on typical EBVpositive aggressive NK-cell leukemia/lymphoma included 2 out of 13 and 2 out of 14 EBV-negative patients. 6,7 One of the small series reported the absence of EBV had no prognostic significance as both EBV-negative patients died of aggressive disease within 1-2 months.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are anecdotal case reports in the literature describing neoplastic proliferation of NK cells with aggressive clinical course but no EBV association. [2][3][4][5]19 Two small series on typical EBVpositive aggressive NK-cell leukemia/lymphoma included 2 out of 13 and 2 out of 14 EBV-negative patients. 6,7 One of the small series reported the absence of EBV had no prognostic significance as both EBV-negative patients died of aggressive disease within 1-2 months.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…To the best of our knowledge, there have been 16 cases reported in the English literature, [2][3][4][5][6][7][8][9] often as single case reports or rare exceptions included in the studies of EBVpositive aggressive NK-cell leukemia/lymphoma. [2][3][4][5][6][7][8] A recent study of a series of seven cases has shown that the EBV-negative aggressive NK-cell leukemia/ lymphoma is indistinguishable clinically and pathologically from EBV-positive counterpart, 9 in contrast to some earlier reports suggesting that patients with EBV-negative aggressive NK-cell leukemia/lymphoma have a less aggressive clinical course and more favorable response to treatment. 2,5,7 Most of the studies on the pathogenesis of NK/ T-cell lymphomas were on extranodal NK/T-cell lymphoma, nasal type, or its cell line derivative, with very limited information on aggressive NK-cell leukemia/lymphoma.…”
mentioning
confidence: 99%
“…(treatment over 17 months, cumulative dose unknown). 13 Thus, a role of a secondary malignancy due to immunosuppressive therapy is possible, although the cumulative doses in our patient were not excessively high, suggesting this is not the only permissive factor.…”
Section: Discussionmentioning
confidence: 55%
“…NK LGLL cells derived from patients had enhanced apoptosis when treated with inhibitors of ERK or MEK [36]. Increased ERK expression has also been identified in aggressive NK leukemia [37]. Tipifarnib is a farnesyltransferase inhibitor targeting Ras family of proteins, although a Phase I/II trial in patients with LGLL was terminated due to the inability to achieve primary endpoints and toxicities [38,39].…”
Section: Aberrant Mechanisms and Directions Of Investigationmentioning
confidence: 99%